PROBLEM BASED LEARNING: PERCEPTION OF NURSING GRADUATES. - dos Santos Almeida, Rodrigo Guimarães; Miranda Coene, Nathália; dos Santos Soldera, Andrezza Gabrielly; Zaleski Braga, Letícia; de Pádua Del Corona, Arminda Rezende (Ciencia, Cuidado e Saude, 2024)
Objective: comprehending how nursing graduates perceive the contribution of the Problem Based Learning (PBL) methodology in the development of their academic training. Method: this is an exploratory descriptive study with a qualitative approach, conducted through semi-structured interview guided by the guiding question: How was the use of the Problem Based Learning method in your professional training? The interviews were recorded and subsequently submitted to Bardin's Content Analysis. Results and Discussion: from the participants' speech, 22 units of significance emerged, which gave rise to seven subcategories, constituents of the three analysis categories: different curriculum structure, advantages for vocational training and obstacles to the implementation of PBL. It provided adequate training, coherent as the Pedagogical Project of the proposed course for professional training, by promoting the development of initiative-taking, critical and reflective attitudes according to the curricular guidelines. The difficulties and challenges refer to the lack of understanding of the pedagogical aspects of the method and the difficulty in organizing the students. Final thoughts: the PBL was recognized as a differential in the teaching-learning process, especially by stimulating learning to learn, which reinforces the importance of keeping the student at the center of the educational process. However, like all pedagogical innovations, the implementation of PBL presented challenges, related to the need for continuous adjustments in the curriculum model.